2018
DOI: 10.1016/j.asej.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of inward solidification inside spherical capsule by using temperature transforming method

Abstract: In this study, a numerical analysis of the inward solidification of phase change material inside spherical capsule is carried out. The spherical capsule that is subjected to convection from the outside surface initially is not at its melting temperature. The control volume approach and temperature transforming method are applied to solve the dimensionless energy equation. The model solution results are validated through a comparison with published experimental data for similar case and it shows a considerably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Figure 6 illustrates the time-wise change of temperature at nine selected spots for three cases considering the aspect ratio W/H = 0.25. At the state of w/o NC (Figure 6A,B,C), the temperature readings at the points (1, 4, 7), (2,5,8), and (3,6,9) overlap over each other. The temperature at Point 7 increases rapidly than the other points since its location near the HTF inlet section.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 illustrates the time-wise change of temperature at nine selected spots for three cases considering the aspect ratio W/H = 0.25. At the state of w/o NC (Figure 6A,B,C), the temperature readings at the points (1, 4, 7), (2,5,8), and (3,6,9) overlap over each other. The temperature at Point 7 increases rapidly than the other points since its location near the HTF inlet section.…”
Section: Validationmentioning
confidence: 99%
“…In addition, they examined different techniques to simulate the heat transfer in the modeling of the phase change problem. In order to attain good performance for TES, the PCM has been packed inside the storage tank with various encapsulation geometries such as a sphere, 8 cylinder, and plate 9 . In some studies related to this topic, Ismail and Henriquez 10 developed a numerical model to examine TES that comprise spherical capsules filled with PCM (water) placed inside a cylindrical tank.…”
Section: Introductionmentioning
confidence: 99%
“…By using the assumptions which are considered in our previous work, 23 the non-dimensional energy balance equation for the spherical container can be formulated as…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The results indicate that increase in the Biot number on the outer surface of the capsule leads to a lower freezing time of water. Asker et al 5 analyzed the inward solidification of PCM with a spherical container. Their results showed that the time of solidification is enhanced as the radius of the container is raised.…”
Section: Introductionmentioning
confidence: 99%